2018
DOI: 10.1021/jacs.8b07366
|View full text |Cite
|
Sign up to set email alerts
|

Sub-picomolar Inhibition of HIV-1 Protease with a Boronic Acid

Abstract: Boronic acids have been typecast as moieties for covalent complexation and are employed only rarely as agents for noncovalent recognition. By exploiting the profuse ability of a boronic acid group to form hydrogen bonds, we have developed an inhibitor of HIV-1 protease with extraordinary affinity. Specifically, we find that replacing an aniline moiety in darunavir with a phenylboronic acid leads to 20-fold greater affinity for the protease. X-Ray crystallography demonstrates that the boronic acid group partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 38 publications
0
57
0
Order By: Relevance
“…[35] Interestingly,i nt his cell-based antiviral assay,i nhibitor 3 did not exhibit appreciable antiviral activity with IC 50 values of 1 mm and 1mm,i nM T-2a nd MT-4 cells, respectively.C arboxamided erivative 4 showed very potent enzyme K i anda ntiviral IC 50 values of 93 nm and 38 nm in MT-2 and MT-4 cells, respectively.B oth carboxylic acid containing inhibitors 11 and 13 showede xcellent enzyme inhibitory activity (K i 7.6 and 3.2 pm,r espectively) however,t hey did not show antiviral activity.B oronic acid derivative 5 has been shown to have very potent enzyme inhibitory activity of 0.5 pm. [26] However,t here is no report of its antiviral activity in ac ell-based assay.W eh ave evaluated the boronic acid PI 5 in an antiviral assay with MT-2 cells. It turned out that boronic acid derivative 5 showedi mproved antiviral IC 50 value of 48.9 nm compared to carboxylic derivatives 3 and 4 (entry 2, Ta ble 1).…”
Section: Resultsmentioning
confidence: 95%
“…[35] Interestingly,i nt his cell-based antiviral assay,i nhibitor 3 did not exhibit appreciable antiviral activity with IC 50 values of 1 mm and 1mm,i nM T-2a nd MT-4 cells, respectively.C arboxamided erivative 4 showed very potent enzyme K i anda ntiviral IC 50 values of 93 nm and 38 nm in MT-2 and MT-4 cells, respectively.B oth carboxylic acid containing inhibitors 11 and 13 showede xcellent enzyme inhibitory activity (K i 7.6 and 3.2 pm,r espectively) however,t hey did not show antiviral activity.B oronic acid derivative 5 has been shown to have very potent enzyme inhibitory activity of 0.5 pm. [26] However,t here is no report of its antiviral activity in ac ell-based assay.W eh ave evaluated the boronic acid PI 5 in an antiviral assay with MT-2 cells. It turned out that boronic acid derivative 5 showedi mproved antiviral IC 50 value of 48.9 nm compared to carboxylic derivatives 3 and 4 (entry 2, Ta ble 1).…”
Section: Resultsmentioning
confidence: 95%
“…The HIV-1 protease is also critical in viral replication, so inhibitors of this enzyme are a good approach for developing HIV antiviral drugs. The drug darunavir is known to be a HIV-1 protease inhibitor and its mechanism of action consists in targeting the S2′ enzymatic subsite, forming hydrogen bonds with the amides present in Asp30 [ 72 , 73 ]. An ideal protease inhibitor must have the ability to interact with three local sides; these include the main chain and side chain of Asp30 and a molecule of water coordinated to the main chain of Gly48.…”
Section: Synthesis and Biological Applications Of Boronic Acids Dementioning
confidence: 99%
“…An ideal protease inhibitor must have the ability to interact with three local sides; these include the main chain and side chain of Asp30 and a molecule of water coordinated to the main chain of Gly48. Based on the knowledge that boronic acids can form strong hydrogen bonds and these bonds are essential for this inhibitory activity, a 4-sulfonylphenylboronic acid (compound 84 ) was designed through replacement of the 4-sulfonylaniline of darunavir, and the effects of this substitution were analyzed [ 72 ]. It was observed that the boronic acid 84 acts as a competitive inhibitor of HIV-1 protease and that the affinity towards the target was 20-fold greater than darunavir (darunavir, K i of 10 pM; boronic acid derivative 84 , K i of 0.5 pM).…”
Section: Synthesis and Biological Applications Of Boronic Acids Dementioning
confidence: 99%
See 2 more Smart Citations